Advances in Hygrothermal Performance of Building Envelopes: Materials, Systems and Simulations 2017
DOI: 10.1520/stp159920160100
|View full text |Cite
|
Sign up to set email alerts
|

Hygrothermal Performance Assessment of Stucco-Clad Wood Frame Walls Having Vented and Ventilated Drainage Cavities

Abstract: The long-term performance in respect to moisture management within any wood frame wall assembly depends on the hygrothermal response of the wall to local climate moisture loads. Estimating the wood moisture content, temperature and time of exposure to conditions suitable for the onset, growth and propagation of mold or rot are critical parameters when assessing the longevity of wood frame structures. A number of approaches to assessing the vulnerability of wood frame structures to deterioration have been devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…It is important to point out that the obtained results for the highest relative humidity in all roofing system considered in this research study were well below 80%. As provided in many previous studies (Hukka and Viitanen, 1999;Viitanen and Ojanen, 2007;Ojanen et al, 2010;Saber et al, 2014Saber et al, , 2016Saber et al, , 2017Saber and Maref, 2015;Lacasse et al, 2016), no risk of condensation and mold growth occurred at different temperatures when the relative humidity is below 80%. Since the highest relative humidities in all black and cool roofs considered in this study (see Figures 6, 7 as examples) were well below 80%, no risk of condensation and mold growth occurred in these roofs.…”
Section: Effect Of Rooftop Short-wave Absorption Coefficient On the Hmentioning
confidence: 63%
“…It is important to point out that the obtained results for the highest relative humidity in all roofing system considered in this research study were well below 80%. As provided in many previous studies (Hukka and Viitanen, 1999;Viitanen and Ojanen, 2007;Ojanen et al, 2010;Saber et al, 2014Saber et al, , 2016Saber et al, , 2017Saber and Maref, 2015;Lacasse et al, 2016), no risk of condensation and mold growth occurred at different temperatures when the relative humidity is below 80%. Since the highest relative humidities in all black and cool roofs considered in this study (see Figures 6, 7 as examples) were well below 80%, no risk of condensation and mold growth occurred in these roofs.…”
Section: Effect Of Rooftop Short-wave Absorption Coefficient On the Hmentioning
confidence: 63%
“…The moisture-related problems can lead to deterioration of roofing materials and affect negatively the thermal performance by means of reduction in overall thermal resistance and service life of the roofing systems. This can lead as well to mold growth in those systems and affect the indoor air quality (IAQ) and the occupants' health and comfort [14,15,[76][77][78][79][80][81][82].…”
Section: Cool Roofs Pros and Cons And Its Relationship With The Weathermentioning
confidence: 99%
“…Most recently, several researchers [14][15][16][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] conducted several studies to investigate the performance of cool and black roofs in terms of energy and moisture when they were subjected to different hot and humid climates in GCC countries. These studies covered several thicknesses of roof insulation material and surface solar reflectivity.…”
Section: Cool Roofs Pros and Cons And Its Relationship With The Weathermentioning
confidence: 99%
“…Researchers who have studied on negative interaction between moisture effect and energy efficiency have concluded that the moisture effect can lead to an increase in annual building energy consumption [24]. In other cases, changes in moisture content and adsorption/desorption (i.e., sorption curve) ability in envelope materials can lead to not only increased/decreased thermal conductivity [25] but also the risk of condensation and mold growth (see [26][27][28] for more details). Neglecting the moisture transport in assessing the overall building performance may lead to inaccurate energy demand predictions [29].…”
Section: Introductionmentioning
confidence: 99%
“…Neglecting the moisture transport in assessing the overall building performance may lead to inaccurate energy demand predictions [29]. There are negative interactions between energy efficiency and moisture effect, which increase the potential for mold growth risk in-built environments with increasing thermal insulation [26][27][28]. Reducing ventilation rates to improve energy consumption in the building can lead to increasing concentrations of contaminants in indoor air, which indicates a negative interaction between energy and indoor air quality parameters [19].…”
Section: Introductionmentioning
confidence: 99%